2022
DOI: 10.1108/vjikms-05-2022-0154
|View full text |Cite
|
Sign up to set email alerts
|

Examining online learning platform characteristics and employee engagement relationship during Covid-19

Abstract: Purpose As work-from-home policies were being implemented during Covid-19, organizations have been migrating their learning and development programs to digital platforms. This study aims to understand the role of employees’ perceptions about four key attributes of online learning platforms (OLPs), namely, online environment, ease of use, online content (OC) and online engagement anchors in their levels of work engagement (WE). Further, it also investigates how the personality attributes of the employees and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Heightened levels of interest and enjoyment can then increase the desire of individuals to immerse themselves in the learning activities. Ghosh et al (2022) believe the extent of employee engagement will be significantly influenced by their opinions of the above OLP attributes. In the present study, the authors focus specifically on the WE dimension of employee engagement.…”
Section: Online Learning Platforms and Key Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heightened levels of interest and enjoyment can then increase the desire of individuals to immerse themselves in the learning activities. Ghosh et al (2022) believe the extent of employee engagement will be significantly influenced by their opinions of the above OLP attributes. In the present study, the authors focus specifically on the WE dimension of employee engagement.…”
Section: Online Learning Platforms and Key Characteristicsmentioning
confidence: 99%
“…To explore the issues further, Ghosh et al (2022) conducted a survey of employees at four Indian IT companies who were working from home. A total of 306 questionnaires were completed and analysis confirmed that all the online personality characteristics (OLPC) discussed above positively affect WE.…”
Section: Study Evidence From Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mobile learning (ML), driven by technological advancements, has become essential in online education, offering flexibility and convenience in accessing learning materials. The COVID-19 pandemic highlighted its significance as n-Learning rapidly replaced traditional classroom settings, demonstrating its ability to sustain education in challenging times and hinting at its potential to reshape future educational models [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research, M-learning has a positive influence on the learning engagement, learning motivation, and learning outcomes of students [6][7][8]. This stems from the ability to access educational resources and interact with learning activities via a personal device, enabling students' learning autonomy and increasing their learning engagement and motivation.…”
Section: Introductionmentioning
confidence: 99%